Formal Specification and Verification of Smart Contract-Based Loan Management System Using TLA+ - Seongho Yoon; Jin-Young Choi (IEEE Access)
Smart contracts provide convenience to the financial industry by automating complex transactions without intermediaries. In the context of decentralized finance, ensuring the correctness, reliability, and efficiency of these automated systems is crucial, especially for loan management processes. This paper presents a formal specification of a smart contract-based loan management system using TLA+. The system is designed to handle various types of loans, including credit-based and collateral-backed loans, managing both regular and early repayments, as well as handling late payments and collateral forfeiture. Our specification defines key components such as loan states, repayment calculations, and collateral management, ensuring that all aspects of the loan lifecycle are rigorously modeled and verified. Safety properties, such as preventing negative loan balances and ensuring proper collateral ownership transfer, are enforced alongside liveness properties that guarantee the system reaches a termination state where all loans are either fully repaid or defaulted. We used the TLC model checker to verify the correctness of the system across all possible states and transitions. The verification process confirmed that the system consistently adheres to its formal specification under a variety of operational conditions. Through the formal specification and comprehensive verification with TLA+, this work enhances the dependability of smart contract based financial systems, providing a secure, verifiable, and resilient loan management framework ready for deployment in real-world DeFi environments.